2016
DOI: 10.3390/ijerph13100954
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Noise Annoyance and Mental Health in Adults: Findings from the Cross-Sectional German Health Update (GEDA) Study 2012

Abstract: The health implications of environmental noise, especially cardiovascular effects, have been studied intensively. Research on associations between noise and mental health, however, has shown contradictory results. The present study examined associations between individual levels of noise annoyance due to noise from various sources in the living environment and mental health of adults in Germany. It evaluated whether these associations persisted after adjusting for potential covariates. Data were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 41 publications
4
66
0
9
Order By: Relevance
“…Recent studies have provided evidence that the degree of noise annoyance induced by exposure to environmental or aircraft noise was associated with a significantly higher prevalence of depression and anxiety in the general population (Beutel et al, 2016;Hammersen, Niemann, & Hoebel, 2016). Schreckenberg, Meis, Kahl, Peschel, and Eikmann (2010) emphasized that determining the physical and mental health of residents exposed to aircraft noise is not simply limited to noise exposure but to noise annoyance .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have provided evidence that the degree of noise annoyance induced by exposure to environmental or aircraft noise was associated with a significantly higher prevalence of depression and anxiety in the general population (Beutel et al, 2016;Hammersen, Niemann, & Hoebel, 2016). Schreckenberg, Meis, Kahl, Peschel, and Eikmann (2010) emphasized that determining the physical and mental health of residents exposed to aircraft noise is not simply limited to noise exposure but to noise annoyance .…”
Section: Resultsmentioning
confidence: 99%
“…Schreckenberg, Meis, Kahl, Peschel, and Eikmann (2010) emphasized that determining the physical and mental health of residents exposed to aircraft noise is not simply limited to noise exposure but to noise annoyance . Recent studies have provided evidence that the degree of noise annoyance induced by exposure to environmental or aircraft noise was associated with a significantly higher prevalence of depression and anxiety in the general population (Beutel et al, 2016;Hammersen, Niemann, & Hoebel, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This cutpoint of 60 is consistent with much psychological research in which the MHI‐5 is used to predict depression (Friedman, Heisel, & Delavan, ; Goral, Lipsitz, Muhsen, & Gross, ; Kelly et al., ; Silveira et al., ). More recently, however, Cuijpers and colleagues () found that the MHI‐5 is a “good screener for mood disorders in the general population,” but they suggest that a score of 54 may be a better and more conservative cutpoint (see also Gillis et al., ; Hammersen, Niemann, & Hoebel, ) . We also take the more conservative path and choose a cutpoint of 54 to measure depression in our sample.…”
Section: Current Studymentioning
confidence: 99%
“…Another reason is the airport noise pollution in this area. Studies have shown that people who live near airports are exposed to a greater extent of various diseases, including mental disorders (33)(34)(35). Mashhad International Airport is the second-high traffic airport in Iran and is located close to the residential areas under the supervision of Health Center No.…”
Section: Discussionmentioning
confidence: 99%